2017
DOI: 10.1186/s12986-017-0233-z
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism and significance of homocysteine in nutrition and health

Abstract: An association between arteriosclerosis and homocysteine (Hcy) was first demonstrated in 1969. Hcy is a sulfur containing amino acid derived from the essential amino acid methionine (Met). Hyperhomocysteinemia (HHcy) was subsequently shown in several age-related pathologies such as osteoporosis, Alzheimer’s disease, Parkinson’s disease, stroke, and cardiovascular disease (CVD). Also, Hcy is associated with (but not limited to) cancer, aortic aneurysm, hypothyroidism and end renal stage disease to mention some.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
236
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(241 citation statements)
references
References 119 publications
(112 reference statements)
2
236
0
3
Order By: Relevance
“…Hcy is a non‐proteinogenic amino acid that forms as an intermediate during the conversion of methionine to cysteine. Previous studies have revealed an association of hyper‐Hcy with several diseases, such as Alzheimer's disease, Parkinson's disease, and stroke . High levels of Hcy are also associated with neuropsychiatric disorders, including autism .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hcy is a non‐proteinogenic amino acid that forms as an intermediate during the conversion of methionine to cysteine. Previous studies have revealed an association of hyper‐Hcy with several diseases, such as Alzheimer's disease, Parkinson's disease, and stroke . High levels of Hcy are also associated with neuropsychiatric disorders, including autism .…”
Section: Discussionmentioning
confidence: 99%
“…Hcy is a non‐proteinogenic amino acid that exerts important roles in human physiology. Hyper‐Hcy was shown to be linked with several diseases in the central nervous system, including Alzheimer's disease, Parkinson's disease, and stroke . Abnormally high levels of Hcy have also been observed in serum and urine samples of autistic children and are considered as a potential diagnostic marker for nutritional deficiency that is associated with improper functioning of autistic children .…”
mentioning
confidence: 99%
“…Hcy is known to be an important biochemical parameter, primarily as a cardiovascular marker, as a determinant of neuronal disorders, renal health, renal failure, diabetes and venous thromboembolism, and even carcinogenesis (Finkelstein et al, 2000;Ravaglia et al, 2005;Wijekoon et al, 2006;Martinez et al, 2017;Ramakrishnan et al, 2006;Kumar et al, 2017). Levels of the advanced biochemical research marker Hcy are a current and reliable tool for the evaluation of the health conditions of humans and animals in different metabolic and endocrinal periods in which the homeostatic continuum of organisms is altered.…”
Section: Discussionmentioning
confidence: 99%
“…Hcy, which mediates methionine metabolism, is catabolized in the reaction with the vitamin B6 cofactor of Cysteine (Cys). In most tissues, Hcy can be converted back to methionine by this re-methylation reaction, catalyzed by the enzyme "methionine synthase," requiring 5-methylene tetrahydrofolate (THF4) in the form of reduced folate as the methyl donor with vitamin B12 cofactor (Finkelstein et al, 2000;Ravaglia et al, 2005;Wijekoon et al, 2006;Ramakrishnan et al, 2006;Martinez et al, 2017;Mohammad et al, 2010;Kumar et al, 2017;Škovierová et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation